2018
DOI: 10.1038/s42005-018-0073-9
|View full text |Cite
|
Sign up to set email alerts
|

Confinement and asymptotic freedom with Cooper pairs

Abstract: One of the most profound aspects of the standard model of particle physics, the mechanism of confinement binding quarks into hadrons, is not sufficiently understood. The only known semiclassical mechanism of confinement, mediated by chromo-electric strings in a condensate of magnetic monopoles still lacks experimental evidence. Here we show that the infinite resistance superinsulating state, which emerges on the insulating side of the superconductor-insulator transition in superconducting films offers a realiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
87
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(88 citation statements)
references
References 41 publications
1
87
0
Order By: Relevance
“…Finally, the name and phenomenon of superinsulation was rediscovered and experimentally detected by one of the authors (vmv) and his collaborators in [11,12] based on the earlier ex-perimental observations [13,14]. Superinsulators where identified in [11] as a low-temperature charge Berezinskii-Kosterlitz-Thouless (BKT) [16,17] phase emerging at the temperature of the charge BKT transition and was derived from the wave function -phase-amplitude duality of the uncertainty principle.Motivated by 't Hooft's beautiful idea [8] and building on the framework proposed in [9], a comprehensive theory of the SIT and superinsulators was developed in [18]. It was shown that in duality to the Meissner effect in superconductors, which constricts the magnetic field lines penetrating a type II superconductor into Abrikosov vortices, in superinsulators, electric flux tubes that linearly bind Cooper pairs into neutral "mesons" form.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, the name and phenomenon of superinsulation was rediscovered and experimentally detected by one of the authors (vmv) and his collaborators in [11,12] based on the earlier ex-perimental observations [13,14]. Superinsulators where identified in [11] as a low-temperature charge Berezinskii-Kosterlitz-Thouless (BKT) [16,17] phase emerging at the temperature of the charge BKT transition and was derived from the wave function -phase-amplitude duality of the uncertainty principle.Motivated by 't Hooft's beautiful idea [8] and building on the framework proposed in [9], a comprehensive theory of the SIT and superinsulators was developed in [18]. It was shown that in duality to the Meissner effect in superconductors, which constricts the magnetic field lines penetrating a type II superconductor into Abrikosov vortices, in superinsulators, electric flux tubes that linearly bind Cooper pairs into neutral "mesons" form.…”
mentioning
confidence: 99%
“…It was shown that in duality to the Meissner effect in superconductors, which constricts the magnetic field lines penetrating a type II superconductor into Abrikosov vortices, in superinsulators, electric flux tubes that linearly bind Cooper pairs into neutral "mesons" form. These electric strings confine fluctuating ±Cooper pair charges completely, thereby impeding electric conductance: Cooper pairs are confined exactly as quarks in hadrons [18], the finite-temperature deconfinement transition for linear potentials coinciding with the 2D BKT transition [19,20]. This established superinsulators as a novel, distinct state of matter.The interpretation of the infinite-resistance state in terms of the superinsulating state dual to superconductivity was fiercely criticized in [21] by questioning the correctness of the microscopic modeling of the superconducting films as a Josephson junction array (JJA) and attacking the treatment of this array by [11].…”
mentioning
confidence: 99%
See 3 more Smart Citations